Network Marketing as Non-Traditional Form of Economic Organization - ЗуеваДарья Сергеевна (Journal of Economic Sociology, 2010)
Network marketing is a way of selling goods with the help of distributors of the net who are attached to each other and work under the common rules established and followed by a company. This paper considers the network marketing as an organization with particular formal and informal rules and mechanism of control. The author compares the network marketing with other organizational forms and logics, including the case of classical bureaucracy and analyzes institutional structure of the network marketing, describes the process of formation the network organization and the role of social capital in it as well as discusses the competitiveness of the network marketing. The empirical data set includes 17 interviews with people engaged in the network marketing and review of the internet forums.